2014
DOI: 10.1007/s00256-014-1859-9
|View full text |Cite
|
Sign up to set email alerts
|

Lateral dislocation and incarceration of the posterior tibial tendon through the distal tibiofibular syndesmosis

Abstract: A case of acute, traumatic, lateral dislocation of the posterior tibial tendon is presented as a unique pattern of posterior tibial tendon dislocation. Several attempts at both closed and open reduction were required to relocate the tendon and reduce the fracture-dislocation. This case is being presented to demonstrate the use of cross-sectional imaging to both recognize the initial bony injury and to identify tendon anatomy and pathology that may not be seen in the operating room with limited visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…the pathway of posterior tibial tendon dislocation in the present case was noticed only during surgery, given that, after the unsuccessful reduction maneuver, no instrumental investigations, such as MRi and/or Ct scans, were performed. After critically analyzing the cases mentioned (13,14), which were characterized by initial unsuccessful attempts to obtain good reduction through surgery that was performed in the absence of information from MRi or Ct scans, and also our own management of the case presented here, we strongly suggest that further investigations, such as MRi and/or Ct scans, should be performed after unsuccessful reduction of an ankle dislocation attempted by means of a closed maneuver under local or general anesthesia. Complications after isolated ankle dislocation are quite common: in particular a 5 to 10° reduction in range of motion is described by several Authors (19,20); post-traumatic osteoarthritis is also frequent (21) with persistent pain or discomfort, especially after increased activity (15), which can necessitate further surgical intervention, like debridement, osteophyte removal, arthroplasty or arthrodesis.…”
Section: J Ointsmentioning
confidence: 86%
See 2 more Smart Citations
“…the pathway of posterior tibial tendon dislocation in the present case was noticed only during surgery, given that, after the unsuccessful reduction maneuver, no instrumental investigations, such as MRi and/or Ct scans, were performed. After critically analyzing the cases mentioned (13,14), which were characterized by initial unsuccessful attempts to obtain good reduction through surgery that was performed in the absence of information from MRi or Ct scans, and also our own management of the case presented here, we strongly suggest that further investigations, such as MRi and/or Ct scans, should be performed after unsuccessful reduction of an ankle dislocation attempted by means of a closed maneuver under local or general anesthesia. Complications after isolated ankle dislocation are quite common: in particular a 5 to 10° reduction in range of motion is described by several Authors (19,20); post-traumatic osteoarthritis is also frequent (21) with persistent pain or discomfort, especially after increased activity (15), which can necessitate further surgical intervention, like debridement, osteophyte removal, arthroplasty or arthrodesis.…”
Section: J Ointsmentioning
confidence: 86%
“…in 2010, Ermis et al (12) reported this same pattern of posterior tibial tendon dislocation and interpositioning of the tendon between the distal tibia and fibula in a tibiotalar fracture-dislocation. trividi et al (13) reported a posterior tibial ten-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the unusual traumatic injuries of the ankle fractures is the interposition of the TPT or flexor digitorum longus tendon which results in irreducible fracture-dislocation in the medial aspect of the ankle. The TPT is an important anatomical structure, which is the most common cause of interposition in irreducible ankle fracture dislocation due to the entrapment of the TPT in the tibiofibular and tibiotalar joints [9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that MRI was a valuable tool for diagnosis and surgical planning. 9,12 Prato et al described the value of ultrasound in the acute phase. 13 Gambhir et al reported a late diagnosis of this pathology, with the formation of a bone spur in the medial malleolus at the avulsion site of the flexor retinaculum.…”
Section: Discussionmentioning
confidence: 99%